Factors associated with multiple births in the United Kingdom during COVID-19: A cross-sectional survey - Yan-Shing Chang; Jessica Jones; Seo Ah Hong; Li-Yin Chien (PLoS ONE, 2026)
Background Women with multiple births may encounter many challenges compared to those with singleton births, especially during the COVID-19 pandemic. This is the first study aiming to investigate the factors associated with multiple births during COVID-19 in the United Kingdom. Methods A cross-sectional online survey was carried out between July and November 2021 with women who were up to 6 months postpartum. Sociodemographic, obstetric, and COVID-19-related factors, and infant feeding and support factors, were employed to assess the association with multiple births. Descriptive statistics and bivariate and multivariable analyses were performed. Results Of 858 eligible participants, 53 had multiple births. Bivariate analysis showed that although socioeconomic and COVID-19-related factors were not associated, preterm birth, Neonatal Intensive Care Unit admission, birthweight, mode of birth, postnatal depression, infant feeding practices, impact of COVID-19 on baby fed with expressed breast milk, no support for infant feeding, infant feeding support from online group were associated with multiple births. In the multiple logistic regression, multiple births were significantly associated with infant formula use (AOR 6.17, 95% CI 2.29–16.57), preterm birth (AOR 5.83, 95% CI 1.99–17.11), caesarean birth (AOR 2.97, 95% CI 1.27–6.97), and birthweight (<2.5 kg: AOR 13.16, 95% CI 4.31–40.20;  > 3.5 kg: AOR 0.11, 95% CI 0.02–0.51). Conclusions Participants with multiple births experienced higher obstetric risks and were more likely to feed with infant formula. These findings underscore the need for routine integration of lactation specialists and the expansion of remote support strategies.